The use of glucan as immunostimulant in the treatment of paracoccidioidomycosis - Meira, D. A.; Pereira, PCM; MarcondesMachado, J.; Mendes, R. P.; Barraviera, B.; Pellegrino, J.; RezkallahIwasso, M. T.; Peracoli, MTS; Castilho, L. M.; Thomazini, I; daSilva, C. L.; Foss, N. T.; et al. (Amer Soc Trop Med & Hygiene, 1996)
A group of 10 patients, nine of them seriously infected with Paracoccidioides brasiliensis (G1), received glucan (beta-1,3 polyglucose) as an immunostimulant intravenously once a week for one month, followed by monthly doses (10 mg) over an ii-month period, together with a specific anti-fungal agent as an immunostimulant. A second group of eight moderately infected patients (G2) was treated with only the anti-fungal agent. Among the patients in G1, there was only one case of relapse compared with five in G2. Values for the erythrocyte sedimentation rate (ESR) showed a significant difference (P < 0.01) post-treatment in G1 patients, when compared with the pretreatment levels. There was also a significant reduction (P < 0.001) in the level of serum antibodies to P. brasiliensis in the G1 patients in post-treatment examinations. The phytohemagglutinin (PHA) skin test showed a positive reaction among the patients in G1 (P < 0.01) post-treatment and there was a tendency towards an increase in the number of CD4+ T lymphocytes in both groups after treatment. The serum level of tumor necrosis factor (TNF) proved to be significantly higher (P < 0.02) in the G1 patients during treatment. In the G1 patients, the correlation between ESR and TNF tended to be negative whereas that between ESR and serum antibodies was positive. The present results indicate that the patients who received glucan, in spite of being more seriously ill, had a stronger and more favorable response to therapy.